Lipid Profile (Total Cholesterol, LDL, HDL, Triglyceride) of Injection Contraceptive Acceptors in Semarang - Surati, Surati; Priyatno, Djoko (Masters Program in Public Health, Universitas Sebelas Maret, Indonesia, 2021)
Background: Hormonal injectable contraceptives are the most common choice taken by women. The 3-month injection of contraception is DMPA, one of the most effective contraceptive methods currently used. Using injectable contraceptives, especially DMPA, influences fat metabolism, especially lipoproteins. Changes in fat metabolism cause disturbances in the balance of blood fat fractions (fluctuation of HDL, LDL and total cholesterol levels) due to hormonal influences. Subjects and Method: Descriptive with an observational design study. Seventy-three women accepted injection contraceptive three months with a usage period of more than three years recorded in the Tlogosari Kulon Community Health Center. They were selected based on sample criteria, including inclusion criteria and exclusion criteria, where these criteria determine whether or not the sample can be used. The dependent was lipid profile (cholesterol, trigliceryd, LDL, HDL). The independent variables was contraceptive injections three months. There are seventy-three respondents. Results: The respondents in this study had 3-month injection contraceptive use of were less than the same as six years of use, namely 41 people, while for use more than the same as seven years there were 32 people and show that most of the research respondents had a lipid profile that was still within normal limits. For the cholesterol levels, 23% is normal, and 76% is abnormal, Trigliceryd level 66% is normal, and 34 % is abnormal. LDL levels 100% is normal, and for the HDL levels, 63% is normal, and 37% is abnormal. Conclusion: Most of the lipid profiles of respondents were normal. However, on cholesterol levels, respondents had more abnormal levels than normal, but for other lipid profiles (Trigliceryd, LDL, HDL), most respondents had normal levels.